Exploring the Effects of Implementing PBL to Develop a Unit Plan about Sports in a 4th Grade English Class at a Public School in Medellín, Colombia. (2018)
ABSTRACT: This action research work aimed to explore the effects of implementing Project-Based Learning approach (PBL) to develop a unit plan about sports in a 4th grade English class at a public school in Medellín, Colombia. PBL was implemented in the classroom as a sequence of team work tasks that guided students’ exploration of their favorite sport, football soccer, and prepared them for an oral presentation about this sport in a sport fair. Throughout this implementation, some activities, such as creating a new sportive character, discovering my favorite sport, and designing a football soccer scale model using geometric figures, were carried out as part of the project. Data collected included interviews with students, cooperating teacher’s checklist and teacher’s journals. Findings of this research revealed that there are some positive effects of implementing PBL in the EFL classroom, such as students’ favorable attitudes towards English, increase of students’ confidence, and their readiness to team work throughout the project.